Decomposing socioeconomic inequalities in contraceptive use among Kurdish women: a cross-sectional analysis of the ravansar cohort study - Ali Kazemi-Karyani; Sina Ahmadi; Jafar Yahyavi Dizaj; Farid Najafi; Moslem Soofi (BMC Public Health)
Abstract Background Access to contraception methods is essential for reproductive health and family planning; however, socioeconomic disparities influence their utilization. This study aimed to examine socioeconomic inequalities in contraceptive use (CU) among Kurdish women in western Iran, using data from the Ravansar Non-Communicable Disease (RaNCD) cohort study. Methods Data from 4,823 married women aged 35 years and older were analyzed, categoriezed by their history of CU. The Wagstaff normalized concentration index was employed to assess income-related inequalities. Two separate models were developed to analyze the contributing factors for the use of temporary contraceptive methods and tubectomy. Decomposition analysis was conducted to identify the contributions of various factors, including age, marital status, age at first pregnancy, number of live births, place of residence, and socioeconomic status (SES). Results The findings revealed that 83.79% of participants had a history of CU. Decomposition analysis indicated that marital status and age were the primary contributors to inequality in the use of temporary contraceptive methods, accounting for 38.93% and 18.55% of the inequality, respectively. In contrast, for tubectomy, marital status and age contributed -81.37% and -38.76% to the reduction in inequality, while the number of live births had a positive contribution of 10.79%. Moreover, women in higher socioeconomic quintiles reported greater use of temporary methods, whereas tubectomy was more prevalent among those in lower socioeconomic groups. Conclusions This study highlights significant socioeconomic inequalities in CU among Kurdish women in western Iran. Higher-income women tend to use temporary methods, while lower-income women more often undergo tubectomy. These disparities underscore the need for targeted interventions. Policymakers should focus on improving access to a variety of contraceptive options and enhancing educational initiatives to promote equity in reproductive health.